Traces of foreign retailers – local knowledge-spillovers and strategy adaption within retail internationalization. Issue 5 (20th October 2018) - Gersch, Inka
ABSTRACT: Since the 1990s certain retail companies have evolved into some of the largest and most dispersed transnational corporations worldwide. However, within the 'new era of retail distribution' retailers are increasingly divesting from foreign markets. This study addresses these recent and under-explored dynamics by revealing the traces transnational retail corporations leave after divesting from a country. It explores the aspect of learning of host market retailers from entering transnational corporations (TNCs) and examines how foreign knowledge is adjusted in the business strategies of these local actors. It takes a fresh empirical slant using qualitative interviews with host market retail managers including former TNCs' subsidiaries operating under domestic ownership. The emerging economy of Turkey serves as an empirical example. The paper finds that foreign retailers transfer firm-specific resources to the local retail through (1) demonstration and imitation, (2) vertical linkages with suppliers, (3) joint ventures and acquisitions, and (4) labor turnover of TNC trained staff. Certain successful local companies adjust the foreign knowledge based on their local knowledge and strengths, their high level of flexibility and deep territorial embeddedness, and create 'hybrid' business strategies. These findings suggest that dynamic capabilities are crucial to successful retailing in an international competitive environment. TNC managers should work with local staff in partnerships of equals and managers of locally operating companies should incorporate new knowledge by hiring TNC trained staff.